Estudio de alternativas de potabilización del agua proveniente de la quebrada Yanacocha para su utilización en la Universidad Técnica Particular de Loja. - Guachisaca Contento, Víctor Eduardo (2015)
The present investigation studies different alternatives to potable the water from Yanacocha gorge. The evaluation of the actual system of provision water was performed at the beginning, with the results concluding that it is necessary to design a new water treatment system, because the useful life of the system has served. In order to establish quality water of the Yanacocha gorge, it developed sampling and analysis of physical, chemical and microbiological parameters, getting in the results good quality of water. So, it was not necessary to conduct a study of alternatives for potable water, but it was decided to select a system for water purification consisting of rapid sand filtration with disinfection through a chlorinator team called PROVITAB 3. After selecting the water treatment system, the design of all its elements was performed, and as a complementary part of the study, it designed the capture, sand trap and driveline. And the budgets, construction drawings, technical specifications and manual operation and maintenance of the system were included.